An Extensive Intramedullary Epidermoid Cyst with a Longstanding History of Paraplegia: A Case Report - Yoon, Sang Hoon; Jahng, Tae-Ahn; Kim, Ki-jeong; Chung, Chun Kee; Kim, Hyun Jib (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Spinal cord tumors still challenge clinicians because of their neurological deterioration before and after surgery. Epidermoid cyst is one of the rare intramedullary lesions producing neurological deterioration in cervical spine and it has been reported four times in the literature. We report the case of an intramedullary epidermoid cyst showing a longstanding history of paraplegia as well as recent slowly progressive tingling paresthesia extending from C4 to T10 and weakness in both hands.
Keywords: epidermoid cyst; intramedullary; cervical